Efficient hardware implementation for lightweight mCrypton algorithm using FPGA - Yasir Amer Abbas; Ahmed Salah Hameed; Safa Hazim Alwan; Maryam Adnan Fadel (Institute of Advanced Engineering and Science, 2021)
The lightweight cryptography is used for low available resources devices such as radio frequency identification (RFID) tags, internet of things (IoTs) and wireless sensor networks. In such case, the lightweight cryptographic algorithms should consider power consumption, design area, speed, and throughput. This paper presents a new architecture of mCrypton lightweight cryptographic algorithm which considers the above-mentioned conditions. Resource-shared structure is used to reduce the area of the new architecture. The proposed architecture is implemented using ISE Xilinx V14,5 and Spartan 3 FPGA platform. The simulation results introduced that the proposed design area is 375 of slices, up to 302 MHz operating frequency, a throughput of 646 Mbps, efficiency of 1.7 Mbps/slice and 0.089 Watt power consumption. Thus, the proposed architecture outperforms similar architectures in terms of area, speed, efficiency and throughput.